EFEKTIFITAS JUS SEMANGKA DAN JUS MENTIMUN TERHADAP PENURUNAN TEKANAN DARAH LANSIA PENDERITA HIPERTENSI - Awaluddin Awaluddin; Yuliana Yuliana (Ensiklopedia of Journal, 2022)
Hypertension is one of the biggest health problems faced in the world. The purpose of this study was to determine the effectiveness of watermelon juice and cucumber juice on reducing blood pressure in the elderly with hypertension. The research method uses a quasi-experimental design with a two group pre-post test design. This research was conducted at the Sidomulyo Inpatient Health Center, Pekanbaru with a total of 20 respondents. Data analysis used dependent t test. The results showed that the average blood pressure before and after consuming watermelon juice was 147.62/90.78 mmHg and 144.16/89.54 mmHg. Meanwhile, the average blood pressure before and after consuming cucumber juice was 148.68/91.52 mmHg and 145.24/91.52 mmHg. There is a significant effect on changes in blood pressure in the elderly with hypertension with a p-value of 0.000. Researchers recommend consuming watermelon juice and cucumber juice to help reduce blood pressure.Keywords: Cucumber, Elderly, Hypertension, Juice, Watermelon.